2014
DOI: 10.1186/1756-3305-7-398
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fingerprinting of the myxozoan community in common carp suffering Swim Bladder Inflammation (SBI) identifies multiple etiological agents

Abstract: BackgroundSwim bladder inflammation (SBI) is an important disease of common carp fingerlings in Central Europe. In the 1980s, its etiology was ascribed to multicellular proliferative stages of the myxozoan parasite Sphaerospora dykovae (formerly S. renicola). S. dykovae was reported to proliferate in the blood and in the swim bladder prior to the invasion of the kidney, where sporogony takes place. Due to the presence of emerging numbers of proliferative myxozoan blood stages at different carp culture sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…The parasites not only use the blood for transport to their target organ but proliferate within it and are present almost all year round ( Fig. 1, [26,28,30]). Sphaerospora molnari is a parasite of the common carp in Central Europe with motile blood stages that provoke a strong immune response [29] and are a likely co-factor for developing Swim Bladder Inflammation [30].…”
Section: Introductionmentioning
confidence: 99%
“…The parasites not only use the blood for transport to their target organ but proliferate within it and are present almost all year round ( Fig. 1, [26,28,30]). Sphaerospora molnari is a parasite of the common carp in Central Europe with motile blood stages that provoke a strong immune response [29] and are a likely co-factor for developing Swim Bladder Inflammation [30].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular evidence has suggested that initial blood stages may occur [ 8 ], as in some other myxosporeans (e.g. [ 16 – 18 ]). Sporogonic stages and spores primarily occur in the pseudobranchs, but have occasionally been detected in other organs in farmed Atlantic salmon, such as the gills, kidney and the liver [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, before S. molnari produces spores it circulates as a multicellular blood stage in the fish host. These blood stages are termed “extrasporogonic”, they proliferate in the host for months and are associated with swim bladder inflammation16.…”
mentioning
confidence: 99%
“…Myxozoan blood stages were first reported in carp in 1976 as “unidentified blood objects”17 and the movement described as “dancing”; only recently SSU rDNA sequencing identified the cells as S. molnari 16. Their dancing movement has also been described as “twitching”18, and is extremely fast, non-directional and produced without tubulin-based cell appendages such as cilia or flagella.…”
mentioning
confidence: 99%